Student Perception of Improvement in Communication and Value in 2 Interprofessional Education Delivery Formats. Issue 2 (March 2016) - Arentsen, Ashley; Welsh, Darlene; Jones, Mikael; Weber, Donna; Taylor, Stacy; Kuperstein, Janice; Rayens, Mary Kay; Salt, Elizabeth
Abstract : A preferred format to deliver interprofessional education (IPE) has not been described. The aim of this study was to compare students' (N = 150) perceived value and improvement in communication between an IPE activity delivered using a comprehensive versus an abbreviated format. Although both formats were perceived by students to improve their communication skills and add value to their education, students indicated the abbreviated format was more effective than the comprehensive format.